Enhanced siderophore production by Pseudomonas aeruginosa and its antagonism against fungal threats in sesame fields - Karthika, T P; Dileep, C (Plant Science Today, 2025)
We succeeded in identifying and isolating three strains of Pseudomonas aeruginosa, namely, P2LA3, N3D3 and KMND3, from the soil of sesame (Sesamum indicum L.) cultivation fields in Onattukara, Alappuzha district, Kerala, India. Further in-depth microbiological studies reveal that the maximum siderophore yield is observed in strain KMND3 (70.9 µM), followed by P2LA3 (54 µM) and N3D3 (27 µM). All these strains showed considerable antagonism against significant sesame fungal pathogens such as Aspergillus flavus, Fusarium moniliforme, F. oxysporum and Rhizoctonia solani. Among these strains, KMND3 proved to be the most effective. Therefore, we focused on this strain for further study to demonstrate the influence of various physico-chemical parameters on siderophore production. This study identified several parameters that enhance production, such as starch as a carbon source, yeast as a nitrogen source and supplementary media containing Cd2+, Mn2+ and Hg2+. In contrast, a high concentration of iron was found to inhibit production. The results of our study confidently highlight the potential of P. aeruginosa strain KMND3 as a successful bio-control agent capable of suppressing fungal pathogens in sesame through siderophore-based mechanisms.